PENENTUAN HARGA PREMI ASURANSI PERTANIAN BERBASIS INDEKS CURAH HUJAN DENGAN MENGGUNAKAN METODE PEMBANGKIT DISTRIBUSI EKSPONENSIAL CAMPURAN - QOSIM, SAYID; DHARMAWAN, KOMANG; HARINI, LUH PUTU IDA (E-Jurnal Matematika; Vol 7 No 2 (2018), 2018)
Agricultural insurance is an insurance in agriculture sector that is relatively newly introduced in Indonesia. Agricultural insurance based on rainfall index is one of the risk management tool to keep farmers in case of crop failure. This study aims to determine the steps in determining the value of rainfall index on agricultural insurance and calculate the value of agricultural insurance premiums based on simulated rainfall index by Stochastic weather generator with mixed exponential distribution. The results of this study provide value if the amount of rainfall 103,71 mm so that the amount of premium payments equal to Rp19.016, and if the rainfall is high 128.35 mm then the amount of premium payment equal to Rp1.088.000.